ANALISIS PERHITUNGAN DAN PENETAPAN PAJAK PENGHASILAN ATAS WAJIB PAJAK YANG MEMILIKI PEREDARAN BRUTO TERTENTU SERTA PELAPORANNYA PADA PT. ARTAMAS PRIMA NUSANTARA - Faisal Amri (Tirtayasa Ekonomika, 2019)
Income tax is the tax imposed on the subject of tax on income received or obtained in the tax year. This study aims to determine whether the calculation and determination of income tax of PT. Artamas Prima Nusantara and its reporting are in accordance with applicable tax regulations. The data analysis method used is a qualitative method with a descriptive approach that describes, describes a situation or data and describes and applies a situation in such a way that conclusions can be drawn to answer existing problems. The results of the calculation, determination, deposit and income tax reporting of PT. Artamas Prima Nusantara in the first semester of 2018 in accordance with PP No. 46 of 2013 while in the second semester the results of calculation, stipulation, deposit, and income tax reporting of PT. Artamas Prima Nusantara in accordance with PP No. 23 of 2018 in which the income tax is imposed in a final and deposited every month and the report is set at the Annual Taxpayer Income Tax Return.